Analysis of genetic variability of the entomopathogenic fungi Beauveria bassiana by RAPO markers - VALDERRAMA-F., ANA MILENA; CRISTANCHO-A., MARCO AURELIO; CHÁVES-C., BERNARDO (Revista Colombiana de Entomología, 2000)
Random Amplified Polymorphic DNA (RAPO) markers were used to examine the genetic variability among Beauveria bassiana isolates from several insect hosts, geographic origin, and different pathogenicity percentages on the coffee berry borer, Hypothenemus hempei (Ferrari). For this purpose the DNA was isolated from ten B. bassiana isolates, one from B. brongniartii and one from Paecilomyces lilacinus, the DNA was amplified randomly with 36 decamers. Amplification products were resolved in agarose gels and 445 reproducible bands ranging in size between 0.36-2.0 kb were scored. For the analysís. the similarity coefficient from Jaccard and the genetic distance from Nei &'.Li were calculated and a dendrogram was constructed using the UPGMA method. The dendrogram was divided into two principal groups, in the first group were placed 90% of B. bassiana isolates that exhibited a certain correlation with the geographic origin. In contrast, there were no correlations between the clusters. the insect host and the coffee berry borer pathogenicity. The B. brongniartii isolate clustered together with B. bassiana, perhaps because this isolate is more closely related to the last species. In the second group it was found B. bassiana Bb 9023. That isolate is different from the other group of Beuveria spp. due to different genetic patterns. The P. lilscinus isolate was completely separated from the group of Beauveria spp. It was possible to recognize RAPO markers useful for the intraspecific differentiation of the entomopathogenic fungí B. bassiana.